Pojęcie właściwego „zakładu karnego” (art. 100 k.k.w.) w perspektywie regulacji krajowych oraz standardów prawnomiędzynarodowych - Pracławski, Adam (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
This publication is devoted to the issues of transferring prisoners between correc-tion units in the light of domestic and international regulations. This problem has be-come the subject of multiple discrepancies in case-law and controversies. In the relevant literature after the amendment to the Executive Penal Code made in 2011, the author tries to ﬁ nd the answer to whether the deletion of the rule of, whenever possible, serv-ing the sentence by the convict in the unit located closest to his or her place of residence shall aﬀ ect the penal system within this scope. At the same time, he draws a number of conclusions towards the applicable provision and its further amendments.
Keywords: kara pozbawienia wolności; przydział skazanych; jednostka poprawcza; klasyfikacja penitencjarna; rodzaje jednostek korekcyjnych; kontakt ze światem zewnętrznym; proces readaptacji skazanych